Rancang Bangun Sistem Informasi Enterprise Resource Planning (ERP) Pada Dinas Kesehatan Kota Medan - Feby Hasanah Ritonga; Raissa Amanda Putri (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The Medan City Health Office faces various challenges in managing human resources and inventory due to manual administrative processes, resulting in data inaccuracies, delays, and low operational efficiency. This study aims to design and implement an Enterprise Resource Planning (ERP) system using Human Resource Management (HRM) and Inventory Management (IM) modules. The research employed a qualitative method with data collection techniques consisting of observation, interviews, and literature study. System development used the Rapid Application Development (RAD) method, which includes requirement planning, workshop design, and implementation stages. The results indicate that the ERP system is capable of integrating employee management, attendance, payroll, training, inventory, and stock management processes. The developed system improves data accuracy, accelerates administrative processes, and supports more effective decision-making. Therefore, the implementation of ERP at the Medan City Health Office can enhance efficiency, transparency, and the quality of healthcare services.